Studi Kuat Tekan Batulanau Berdasarkan Uji Lapangan dan Uji Laboratorium Pada Formasi Kampungbaru dan Pulaubalang Daerah Kutai Kartanegara Kalimantan Timur - Kasdi Kasdi; Revia Oktaviani; Agus Winarno (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Rock strength is the ability of a rock to maintain its strength until it breaks when a force is applied. Rock compressive strength is a very important parameter in the world of mining. The compressive strength of the rock determines the mining method that will be used. Several things that influence the compressive strength of rock include porosity, true specific gravity, and water content. With the same volume, if the porosity value is high, the true specific gravity value will be low because of the large number of pores in the rock. This allows the compressive strength value to be low because the rock will crumble more easily when pressure is applied. After testing, the highest compressive strength value was in the Pulaubalang Formation, location 2, with a value of 2.19 MPa. Meanwhile, the lowest compressive strength value was in the Kampungbaru Formation, location 1, with a value of 1.49 MPa. In accordance with the stratigraphic layers in the Kutai Basin, the Pulaubalang Formation is older than the Kampungbaru Formation.